PENINGKATAN AKTIVITAS BELAJAR DALAM PEMBELAJARAN TEMATIK MENGGUNAKAN PENDEKATAN SAINTIFIK KELAS 1 SEKOLAH DASAR - Yani, Suma Tita; Uliyanti, Endang; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve student learning activities in thematic learning by using a scientific approach to first grade students of Sibau Hilir 08 Public Elementary School. The research method used is descriptive method with the form of classroom action research. The subject of this study are teacher as researchers and first grade students totaling 14 students. Data collection technique in this study are observation technique and documents analyze technique. The research instrument used is observation sheets and documents analyze sheets. This result of this study indicate that the use of scientific approach in thematic learning can improve the learning activities of first grade students of Sibau Hilir 08 Public Elementary School.This can be seen from the increase in the percentage of students learning activities in thematic learning using a scientific approach that is in the 1st cycle by 50,00% Â with good enough criteria increased by 12,88% in the 2nd cycle to 62,88% with good criteria, then increased againby 12,83% in the 3rd cycle to 75,71% with very good criteria.Â Keyword : Learning Activities, Scientific Approach, Thematic LearningÂ